2007
DOI: 10.1080/15257770701548980
|View full text |Cite
|
Sign up to set email alerts
|

2′,4′-BNANC: A Novel Bridged Nucleic Acid Analogue with Excellent Hybridizing and Nuclease Resistance Profiles

Abstract: Oligonucleotides modified with 2 ',4 '-BNA(NC) (N-H)/(N-Me) monomers exhibited excellent hybridizing and nuclease resistance properties. Duplex and triplex thermal stabilities were greatly enhanced by incorporating 2',4'-BNA(NC) (N-H) and (N-Me) monomers and nuclease resistance was tremendously higher than that of natural oligonucleotide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…BNA is a third generation nucleic acid analog with excellent mismatch discriminating power and is considered more potent in blocking. Its strong nuclease resistant properties coupled with a 3′ phosphate also prevents amplification of the wild-type DNA and selectively amplifies mutant DNA [11, 12]. The resulting WTB-PCR product can then be sequenced by traditional Sanger sequencing methods.…”
Section: Introductionmentioning
confidence: 99%
“…BNA is a third generation nucleic acid analog with excellent mismatch discriminating power and is considered more potent in blocking. Its strong nuclease resistant properties coupled with a 3′ phosphate also prevents amplification of the wild-type DNA and selectively amplifies mutant DNA [11, 12]. The resulting WTB-PCR product can then be sequenced by traditional Sanger sequencing methods.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work was to inhibit production of this enzyme in the A. baumannii A155 clinical strain using antisense BNA NC -DNA co-oligomers complementary to the region of initiation of translation. We selected BNA NC -DNA molecules as antisense molecules because of their high affinity of binding to the sense molecule, their specificity, which may lead to a highly efficient and selective inhibitory effect, and their low toxicity (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…New analogs related to LNAs, the 2=,4=-bridged nucleic acid-NC (BNA NC ) analogs ( Fig. 1), that exhibit advantages such as higher binding affinity to a cRNA and excellent single-mismatch discriminating ability, have been recently introduced (24). Furthermore, tests carried out in mice showed that BNA NC -based antisense molecules have minimal toxicity (25).…”
mentioning
confidence: 99%
“…Exhaustive listings and a description of oligonucleotide analogs and their applications can be found in recent reviews [3,6,16,23,25,26,27]. A derivative of LNA, 2′- O ,4′-aminoethylene bridged nucleic acid (BNA), also known as 2′,4′-BNA NC (BNA NC ) [28,29,30,31] (Figure 1) has been recently introduced and other derivatives have followed or are in development. As a consequence, LNA is considered the earliest generation of bridged nucleic acids (BNA).…”
Section: Oligonucleotides and Analogsmentioning
confidence: 99%